Design of DCT Launch Control - Mo Chongxiang; Li Dianpeng; Wang Kaiguo; Deng Xiaofeng (Jixie chuandong)
With unique configuration characteristic,the dual- clutch transmission（ DCT） makes the vehicle get a good result in power performance,fuel economy and drivability,and recently it becomes a new development trend in the field of transmission. Basing on analysis of launch control theory of DCT,five phases about launch active control are proposed and vehicle power calculations corresponding to those each control phase are also proposed. It proves that this control strategy can make the vehicle launch in effect and also get a good result of drivability through the test according to the design.